1989
DOI: 10.1128/jvi.63.2.624-630.1989
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus early region 4 is essential for normal stability of late nuclear RNAs

Abstract: H2dl808 is a deletion mutant of adenovirus type 2 lacking most of transcriptional early region E4. In most normal adenovirus host cells this virus displayed a complex mutant phenotype that included a dramatic reduction in the level of cytoplasmic late RNA, a corresponding defect in late protein synthesis, and a 5-to 10-fold defect in viral DNA accumulation. H5dl1004 is a deletion mutant of adenovirus type 5 that also lacks a portion of E4. It exhibited a reduction in levels of cytoplasmic late RNAs that was so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 32 publications
(41 reference statements)
2
42
0
Order By: Relevance
“…The present experiments were not designed to examine this question in detail. However, interactions between the E4orf6 and E1B 55-kDa proteins have been linked to shutoff of host cell protein synthesis and stabilization and transport of viral mRNA (1,2,12,21,30,43,44,50,52,63). It was possible that such inhibition plays a role in the drop in p53 levels, as suggested in an earlier study (20).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present experiments were not designed to examine this question in detail. However, interactions between the E4orf6 and E1B 55-kDa proteins have been linked to shutoff of host cell protein synthesis and stabilization and transport of viral mRNA (1,2,12,21,30,43,44,50,52,63). It was possible that such inhibition plays a role in the drop in p53 levels, as suggested in an earlier study (20).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, one role of E1B products in both productive infection and cell transformation appears to be to prevent untimely E1A-induced cell death, thus permitting production of high yields of progeny or survival of transformants. In productively infected human cells, the E1B 55-kDa polypeptide also interacts with the E4orf6 protein to form complexes which enhance accumulation and transport of late viral mRNAs and induce shutoff of host cell protein synthesis (1,2,8,12,21,30,43,44,50,52,63).…”
mentioning
confidence: 99%
“…In cells infected with a virus that cannot express the 55-kDa E1B protein (E1B-55 kDa) cellular mRNA is exported from the nucleus at near normal rates whereas viral mRNA fails to be transported (40,53). A similar phenotype is observed in cells infected with a virus that cannot express the 34-kDa protein of E4 (E4-34 kDa) (28,60,61). Because the phenotype of viral mutants unable to express both proteins is no more severe than that of viruses unable to express either E1B-55 kDa or E4-34 kDa protein (9,14), it has been proposed that a complex composed of the E4-34 kDa protein and the E1B-55 kDa protein is responsible for usurping the control of mRNA transport during an Ad infection.…”
mentioning
confidence: 87%
“…Late viral transcripts with unused splice donor sites were more dependent on the E1B-55 kDa protein for efficient transport than fully spliced transcripts (39). The work of Ketner and associates has suggested that both the E4-34 kDa protein and the E4 ORF3 (open reading frame 3) protein enhance the stability of the viral RNA in the nucleus (8,9,60,61). Additional studies have further suggested that the ORF3 protein and the 34-kDa (ORF6) protein of E4 express partially overlapping functions with respect to viral growth (30).…”
mentioning
confidence: 99%
“…A similar cellular transforming or oncogenic function has also been linked to E4-ORF1 (19)(20)(21)(22)(46)(47)(48). E4-ORF6 and E4-ORF3 have also been shown to be involved in altering mRNA expression at a posttranscriptional level (39)(40)(41)(42)(43)(44). In addition, E4 products are involved in controlling the cellular transcription factor E2F (38), in E1A-induced p53-independent apoptosis (34), in modulating the phosphorylation status of cellular and viral proteins (28,35) and have recently been shown to alter the nuclear transport of other proteins (17).…”
mentioning
confidence: 95%